Dancing the rainbow nation as it bleeds: the Surialanga Dance Company in post-apartheid South Africa. Issue 2 (3rd July 2019) - Radhakrishnan, Smitha
ABSTRACT: This article analyzes the work of the Surialanga Dance Company of Durban, South Africa, which debuted at Nelson Mandela's inauguration in 1994. Inspired by Mandela's vision of intercultural harmony and created through sustained engagement with Zulu culture, Surialanga created a uniquely South African version of Indian classical Bharatanatyam that threatens colonial and apartheid constructs of "pure" Indian identity. But the company's powerful decolonial message has become less resonant in a post-apartheid context that continues to be structured by what Ndlovu-Gatsheni has called the "colonial matrix of power, " a legacy of colonialism and apartheid that results in a narrow focus on ethnic and racial identities. Drawing both from direct participation and interviews with the director and company members (2001–2008; 2018), this article traces the history of Surialanga's decolonising praxis from Mandela's inauguration to the present, arguing for the continued salience of Surialanga's dance, even in the face of particularism and violence.